Analysis of Annual and Monthly Temperature Fluctuations in Makkah for the Period 1950–2023 - Alamro, Njoud Abd Alaziz; Almohamad, Hussein Ahmed (Journal of Humanities & Social Sciences, 2025)
This study analyzes the changes in the mean maximum and minimum temperatures at both the monthly and annual levels to identify the prevailing climatic patterns in Makkah and provide detailed information that aids in informed decision-making. The research problem revolves around understanding the spatial variability of temperature fluctuations in Makkah and identifying the contributing factors. One of the study's hypotheses suggests a general trend of increasing maximum and minimum temperatures in Makkah during the period from 1950 to 2023, with variations in the rate of increase across different time periods.The study aims to determine the overall trend of temperature changes from 1950 to 2023, utilizing climate records from the Climatic Research Unit (CRU) at the University of East Anglia. It adopts historical and analytical methodologies, along with statistical approaches for temperature analysis. The study period is divided into seven decades, each consisting of ten years, followed by statistical analysis using standard deviation and graphical representation in Excel. The data is then mapped using ArcMap software.The findings indicate that temperature fluctuations in Makkah over seven decades have been minimal and unnoticeable, with a general increasing trend in mean maximum temperatures, showing a decadal increase rate of 0.206°C. Similarly, mean minimum temperatures have exhibited an increasing trend, with a decadal rise of 0.166°C. The maximum and minimum temperature averages followed a similar pattern of rise and fall, increasing during the period (2011–2023) and decreasing during (1961–1970). The monthly mean maximum temperature for the study period was 35.75°C, while the mean minimum temperature was 23.36°C.
Keywords: Climate change; temperature trends; Makkah climate; temperature variability; maximum and minimum temperatures; historical climate analysis; climatic research; sustainable environment; statistical climate analysis; ArcMap